Place, race and politics : the anatomy of a law and order crisis - Weber, Leanne; Blaustein, Jarrett; Benier, Kathryn; Wickes, Rebecca; Johns, Diana F. (Emerald Publishing Limited, 2021)
Place, Race and Politics presents an integrated analysis of the social and political processes that combined to construct a media-driven 'crisis' concerning African youth crime in the city of Melbourne, Australia. Combining original research and analysis alongside published sources, the authors carefully dissect the anatomy of a racialized and politicized public discourse and delve into the profound impact of this on African-Australian communities in Melbourne. Drawing on political and media analysis and community-based research, the authors investigate how South Sudanese Australians in Melbourne came to be identified, supposedly, as a unique threat to community safety, the role played by the media, state and federal politics, the policing and perceptions of race in this process, and the physical and emotional impacts on affected communities of the law and order crisis concerning 'African crime'. While deeply rooted in local conditions, the book resonates with similar examples of the criminalization and othering of racialized communities, the surveillance and exclusion of 'crimmigrants', and with popular punitivism and the rise of far-right politics globally in response to deeply felt anxieties about rapid social, economic and cultural change.